Pelatihan Penulisan Artikel Ilmiah dan Publikasi di Jurnal bagi Guru SMAN 4 Tualang, Kabupaten Siak - Marwa Marwa; Marta Dinata (Universitas Mathla'ul Anwar Banten, 2020)
WRITING SCIENTIFIC ARTICLES AND PUBLICATIONS TRAINING IN JOURNALS FOR TEACHERS OF SMAN 4 TUALANG, SIAK REGENCY. The training of the article writing and journal publication was held in SMAN 4 Tualang, Kabupaten Siak-Riau due to teachers’ problems covering the lack of article writing knowledge, low motivation and awareness of the importance of conducting research and its dissemination particularly for teachers’ professional development. Moreover, the teachers did not know much about journals information whereby they could publish their article writing. Therefore, the outreach community team from Faculty of Education and Teachers’ training, Universitas Lancang Kuning Pekanbaru conducted this program in order to solve the teachers’ problems. This training was conducted in one day (8 hours) consisting of two sessions. In the first session (8-12 a.m.), the participants were given the materials about the essence, elements, and knowledge of article writing followed by making article draft (how to make a good title, abstract and introduction). In the second session (1-5 p.m.), the trainer gave materials pertaining to how to deal with publication process from registration, login, and article online submission in journals. The simulations were given as the trainer guided the participants to register to ELT Lectura FKIP Unilak Journal, Bio-Lectura Journal, and Lectura: Journal Pendidikan UNILAK, login, check and read information in the journals. In short, this training facilitated the SMAN 4 Tualang teachers’ knowledge and skills of article writing and they know how to publish their articles. The outreach team suggests future outreach community program conduct the same activity since there are many school teachers need the training of article writing and publication in journals.